Reflections on Minimal Adversariality - Govier, Trudy (Informal Logic, 2021)
Beginning with my 1999 account in The Philosophy of Argument, this essay explores views about adversariality in argument. Although my distinction between minimal and ancillary adversariality is widely accepted, there are flaws in my defense of the claim that all arguments exhibit minimal adversariality and in a lack of sensitivity to aspects of gender and culture. Further discussions of minimal adversariality, including those of Scott Aikin, John Casey, Katharina Stevens and Daniel Cohen, are discussed. The claim that all argument are adversarial in at least a minimal sense is defended due to its connection with arguers’ intent to support their conclusions.